POLA PERILAKU PELAKU USAHA DALAM PENGHINDARAN KEWAJIBAN PAJAK (TAX AVOIDANCE) - Layly Dwi Rohmatunnisa' (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2022)
The existence of Micro, Small and Medium Enterprises (MSMEs) is expected to be able to contribute to state revenues through the tax sector. The purpose of this study was to determine the profile of the poultry business, the meaning of tax compliance for poultry businesses, tax avoidance behavior in poultry businesses, and to find out the efforts to overcome tax avoidance behavior in business actors. poultry in Blitar Regency. This research is a qualitative research or naturalistic paradigm using an interpretive paradigm through Husrell's transcendental phenomenological approach. The results of the study found that the tax compliance of poultry businesses in Blitar Regency was very low. This is due to the view that the tax rate is too large, namely the rate of 0.5% multiplied by turnover per year.